USING KEYWORDS AND SPECIAL COMMANDS IN THE GOOGLE INTERNET SEARCH SYSTEM - Ilkhom Dustnazarovich Ganiev (Web of Journals Publishing, 2023)
Today, the number of users of search engines on the Internet is very large. However, the number of users of some keywords and special commands in the search engine is low. This article discusses the use of keywords and special commands in the Google Internet search engine.
Keywords: Google, Yahoo, Rambler, Yandex, system, operator.